IMPLEMENTASI PELAKSANAAN WAJIB DAFTAR PERUSAHAAN DI KOTA SURABAYA - Nada Nabila Fauzi; Mas Anienda Tien F. (HUKMY : Jurnal Hukum, 2025)
This study was investigates the implementation of Law No. 3 of 1982 on Mandatory Company Registration in Surabaya, focusing on the corporate sector. Through comprehensive analysis, the research aims to evaluate company compliance with registration regulations, identify implementation issues, and formulate strategic recommendations for improvement. The methods include secondary data analysis and field surveys with company owners and managers. Findings reveal variations in compliance levels, with some companies adhering well to the regulations, while others face challenges such as lack of understanding of registration procedures. Recommendations include enhancing company owners understanding of Law No. 3 of 1982, providing procedural guidance, and strengthening collaboration between companies and authorities. This research is expected to contribute to improving corporate compliance and regulatory effectiveness in Surabaya.